Fisherman's acceptance of information and communication technology integration in Malaysia: exploring the moderating effect of age and experience - Zaremohzzabieh, Zeinab; Abu Samah, Bahaman; Omar, Siti Zobidah; Bolong, Jusang; Mohamed Shaffril, Hayrol Azril (Asian Network for Scientific Information, 2014)
This study used Structural Equation Modeling (SEM) design, in which 400 Malaysia fishermen from the four fishery districts namely Langkawi Island, Besut, Larut-Matang and Mersing were administered to explore the factors that influence their acceptance of Information and Communication Technology (ICT) integration in Malaysia. The aim of this study was twofold: The primary purposes was to test the Unified Theory of Acceptance and Use of Technology (UTAUT) including performance expectancy (PE), effort expectancy (EE), social influence (SI) and facilitating conditions (FC) in the prediction of behavioral intention to use ICTs among Malaysia fishermen. Second, explore the moderating effects of age and experience linked between predictors and behavioral intention based on multi-group analysis. The findings of this study clearly show the model accounts for almost 25% of the variance in user intentions, with FC, PE and EE surfacing only as the key determinants for their behavioural intentions of ICT usage. In an additional analysis revealed that age significantly moderates purposed relationship between the overall UTAUT constructs and behavioral intention while the moderating effect of experience was only established in PE and EE. Finally, the result suggests support for the application of the model in studying the acceptance of ICT in fishing communities. The factors were found to be significant in this study should be taken into account in the implementation of ICT projects and another validation of the ICTs research model in similar research institutions in Malaysia is advised.